ChemInform Abstract: From Diols to Lactones under Aerobic Conditions Using a Laccase/TEMPO Catalytic System in Aqueous Medium. Issue 20 (25th April 2013) - Diaz‐Rodriguez, Alba; Lavandera, Ivan; Kanbak‐Aksu, Seda; Sheldon, Roger A.; Gotor, Vicente; Gotor‐Fernandez, Vicente
Abstract The laccase/TEMPO catalyzed aerobic oxidation of 1, 5‐diols to lactones in aqueous media is reported.